The mechanism of salt effects on starch gelatinization from a statistical thermodynamic perspective. (February 2019) - Nicol, Thomas W.J.; Isobe, Noriyuki; Clark, James H.; Matubayasi, Nobuyuki; Shimizu, Seishi
Abstract: Understanding the gelatinization of starch requires a theoretical framework that can extract microscopic information from the literature's abundant experimental data in a quantitative manner. Recent developments in statistical thermodynamics have been adapted here to extract the starch-water and starch-salt affinity changes that occur during gelatinization, in a manner beyond the capabilities of traditional polymer theory. We have clarified the mechanism that leads to the increases of salt binding upon gelatinization at high concentrations. Contrary to previous assumptions, salt-starch affinity has been shown to be predominant in the salt effect on gelatinization over water structure contributions. How the temperature of gelatinization depends on salt concentration can be rationalized by the exclusion of salts at low salt concentrations from the gelatinized state and salt anion accessibility to the inside of the starch granule at increased concentration. Finally, the salt anion accessibility informs whether gelatinization progresses from the hilum or the periphery of the starch granule. Graphical abstract: Image 1 Highlights: How salts affect starch gelatinization on a molecular basis is clarified. Solvation effect beyond the reach of the Flory theory can be clarified directly from calorimetry. Salt exclusion from starch key at low concentration. Salts' accessibility to starch and consequent binding crucial at higher salt concentration. Anions play a major role on salt-starch interaction.